Sacrificial Worship in The Perspective of Islamic Law and The Challenges of Animal Rights and Veganism - Pradana, Muhammad Riezky; AlMubaroq, Misbakhul Munir (STAINI Press, 2026)
The practice of Qurban is a fundamental part of Islamic teachings, carrying both spiritual and social values. Spiritually, it reflects submission to Allah SWT, while socially, it promotes care and generosity toward the less fortunate. Conducted annually during Eid al-Adha, Qurban has been practiced since the time of Prophet Ibrahim AS and holds a significant place in Muslim communities. However, in contemporary discourse, this ritual has faced criticism, particularly from animal rights activists and vegan advocates who see animal slaughter as exploitation and cruelty toward sentient beings. This raises questions about whether Islamic traditions align with modern principles of animal welfare. This article explores Qurban from the perspective of Islamic law and examines how Islamic teachings respond to the ideological challenges posed by animal rights and veganism. Using a normative approach and library research method, it analyzes Qur’anic texts, Hadith, classical and modern Islamic jurisprudence, and fatwas. The findings show that Islam upholds strong ethical guidelines in animal treatment, emphasizing ihsan (compassion), requiring that animals be slaughtered with kindness and proper procedure. Thus, when conducted ethically, Qurban aligns with animal welfare principles. The study encourages constructive dialogue between religious values and modern ethics in a multicultural society.